The Indian milk collection centre: a one-stop shop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
T.P. Rama Rao explains how an ingenious, smart card-based computer system is helping Indian farmers to improve their dairy herds and the quality and quantity of their milk.